Analysis of Business Communication to Build the Brand Image of the SME “Citra Rasa” in Majalengka - Wafa Nidaul Haq; Farida Nurfalah; Novicky Alban Adiputra (Green Publisher Indonesia, 2026)
Citra Rasa is an MSME (Micro, Small and Medium Enterprises) that has products with unique flavors located in Majalengka City, but its use of business communication, especially digital media for marketing communication, is still not optimal. This study to investigate the pattern of business communication that carried out by Citra Rasa SME, consumer perception towards image brand, and sustainability business on local market. This research uses descriptive qualitative method, data collection techniques performed are observation, in-depth interviews and documentation. The research informants included SME owners, employees and regular customers. Analysis was performed using Bovee & Thill’s business communication theory and John Elkington’s triple bottom line framework. The results show that communication of product information is still primarily through face-to-face, and consumer perceptions of brand image are moderately good; however, the use of digital media remains to be optimized, which affects business sustainability in the aspects of customer loyalty and repurchase. In conclusion, Citra Rasa SME still relies heavily on face-to-face communication, while digital media use remains minimal, resulting in suboptimal brand image building. From the Triple Bottom Line perspective, business sustainability is supported by profit (stable sales), people (good social relations), and planet (basic production cleanliness). Therefore, Citra Rasa SME needs to optimize digital media, improve packaging, introduce product variations, and manage social media more aggressively to enhance brand image and ensure long-term sustainability.